The 100 Most Influential Painters & Sculptors of the Renaissance - Edited by Kuiper, Kathleen (New York Britannica Educational Pub., 2010)
The Renaissance was a fantastic period of rebirth in terms of art and culture. This book recounts the struggles and victories of the most celebrated artists who lived and worked at this time. The masterpieces of Leonardo da Vinci, Pieter Bruegel, Sandro Botticelli, and many others also highlighted. Readers will be swept up in the fervor and change of the poque, which is fully supported with beautiful photographs and detailed illustrations.
Includes Glossary, Illustrations and index.
Keywords: Painters -- Biography